Answer:
x=2; y=3
Step-by-step explanation:
You first add 3y to both sides. Divide both sides by 6. Then subsitute to get your answer.
The answer is:
a: 1 = 2(x^2<span> + 2</span>x<span>)
b:</span>1 = 2x^2 + 4<span>x
d:</span>3 = 2(x + 1)^2
you can tell these are your answer when you solve it.
Hope this helps!
Newton's law of motion has three parts. The second of which states that the force needed to move an object is directly proportional to the acceleration of the motion. The proportion can be written as,
F = ka
where k is the constant of proportionality. This can be substituted with the mass of the object such that the equation would become.
F = ma
where F is force, m is mass, and a is acceleration.
18144 divided by 8 Distributive property
Answer:
11.7
Step-by-step explanation: